Antecknat: Det mångfacetterade kulturbegreppet - Gunnarsson Payne, Jenny (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2012)
In 1982, ethnologists Billy Ehn and Orvar Löfgren rhetorically asked whether the concept of culture could mean anything, and whether it would not be wiser to just stick to one definition of it. Some thirty years later, it has become quite clear that the concept of culture is still one of our most multi-faceted concepts. With Johan Fornäs’ recent book Kultur (Culture) as its starting point, this text discusses two different models that have recently been developed to provide an overview over the plethora of understandings of ”culture”. It argues that Johan Fornäs’ model serves an important pedagogical purpose, but suggests that Magnus Öhlander’s multi-theoretical model suits the discipline of ethnology somewhat better.